2017
DOI: 10.3847/1538-3881/aa725f
|View full text |Cite
|
Sign up to set email alerts
|

K2-66b and K2-106b: Two Extremely Hot Sub-Neptune-size Planets with High Densities

Abstract: We report precise mass and density measurements of two extremely hot sub-Neptune-size planets from the K2 mission using radial velocities, K2 photometry, and adaptive optics imaging. K2-66 harbors a close-in subNeptune-sized ( -+ 2.49 0.24 0.34 Å R ) planet (K2-66b) with a mass of  21.3 3.6 Å M . Because the star is evolving up the subgiant branch, K2-66b receives a high level of irradiation, roughly twice the main-sequence value. K2-66b may reside within the so-called "photoevaporation desert," a domain of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 105 publications
0
31
0
Order By: Relevance
“…This type of interior structure is believed to be common among super-Earths and sub-Neptunes discovered by Kepler and K2 since RV observations have shown that most of these planets larger than about 1.6 Å R have densities too low to be explained by rocky compositions Weiss & Marcy 2014;Dressing et al 2015;Rogers 2015;Sinukoff et al 2017a). Due to its short (19 hr) orbital period, WASP-47 e is so highly irradiated that any hydrogen/helium envelope would quickly be lost via photoevaporation (Penz et al 2008;Sanz-Forcada et al 2011;Lopez et al 2012), so any envelope around WASP-47 e must be made of water or some other highmetallicity volatile material (Lopez 2017).…”
Section: Constraints On the Composition Of Wasp-47 Ementioning
confidence: 86%
“…This type of interior structure is believed to be common among super-Earths and sub-Neptunes discovered by Kepler and K2 since RV observations have shown that most of these planets larger than about 1.6 Å R have densities too low to be explained by rocky compositions Weiss & Marcy 2014;Dressing et al 2015;Rogers 2015;Sinukoff et al 2017a). Due to its short (19 hr) orbital period, WASP-47 e is so highly irradiated that any hydrogen/helium envelope would quickly be lost via photoevaporation (Penz et al 2008;Sanz-Forcada et al 2011;Lopez et al 2012), so any envelope around WASP-47 e must be made of water or some other highmetallicity volatile material (Lopez 2017).…”
Section: Constraints On the Composition Of Wasp-47 Ementioning
confidence: 86%
“…We felt a homogeneous analysis was warranted because the results in the literature were reported by different groups using different procedures to determine the stellar parameters and to mitigate the effects of timecorrelated noise in the radial-velocity data. For example, K2-106b was reported by Guenther et al (2017) to have an iron mass fraction of 80 +20 −30 %, while Sinukoff et al (2017) concluded that the composition was compatible with that of the Earth (35% iron). For this work, we combined all the previously published datasets, used the parallaxes from Gaia Data Release 2 (Gaia Collaboration et al 2018) to refine the stellar parameters, and employed a Gaussian Process framework to disentangle planetary radial velocity signals from cor-related noise.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the remnant cores of Neptunian or Jovian planets could be > 10M ⊕ . The possibility of very heavy cores is also supported by the discovery of rocky mega-Earths such as BD+20 594 b which has a mass and radius of 16.3 ± 6.0M ⊕ and 2.2 ± 0.1R ⊕ (Espinoza et al 2016) or K2-66 b with 21.3 ± 3.6M ⊕ and 2.50 ± 0.3R ⊕ (Sinukoff et al 2017) respectively. Therefore whilst the critical mass Υ β ∼ 10M ⊕ , the probabilistic function Γ γ could range from 10 − 25M ⊕ according to observations and theoretical predictions.…”
Section: Planetary Parametersmentioning
confidence: 92%